P. granatum Peel Polysaccharides Ameliorate Imiquimod-Induced Psoriasis-Like Dermatitis in Mice via Suppression of NF-κB and STAT3 Pathways - Chen, Haiming; Wang, Cheng; Tang, Bin; Yu, Jingjie; Lu, Yue; Zhang, Junhong; Yan, Yuhong; Deng, Hao; Han, Ling; Li, Shaoping; Lu, Chuanjian (Frontiers in Pharmacology, 2022)
Psoriasis is a chronic and refractory inflammatory and autoimmune-mediated cutaneous disease affecting approximately 2%–3% of the global population. Most of the current therapies could relieve symptoms rapidly, while the side effects cannot be negligible. Hence, it is urgent to explore much safer and more effective treatments. In the current work, we evaluated the potential beneficial effect of Punica granatum peel polysaccharides (PPPs) in an imiquimod-elicited psoriasis-like mouse model and unraveled their mechanism of action. Firstly, PPPs were isolated from P. granatum peels, and then the molecular weight was determined and monosaccharide analysis was performed. The results revealed that PPPs significantly ameliorated psoriasis-like skin lesions and reduced the Psoriasis Area and Severity Index (PASI) scores and transepidermal water loss (TEWL). PPPs also attenuated the expressions of CD3 and Ki67 in psoriasis-like mouse skin and suppressed the serum or skin levels of pro-inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), IL-1β, IL-8, IL-17, and IL-23. Moreover, PPPs were able to upregulate the mRNA and protein expressions of aquaporin-3 (AQP3) and filaggrin (FLG) in the skin of mice. In addition, PPPs inhibited the NF-κB and STAT3 signaling pathways. Overall, these results indicated that PPPs ameliorated the symptoms of psoriasis through inhibition of the inflammatory cytokines by suppressing the NF-κB and STAT3 signaling pathways and improved skin barrier protection via enhancing AQP3 and FLG. These observations potentially contribute to providing theoretical and experimental evidence for the clinical application of PPPs for psoriasis.